Evidence for deceleration in the radio jets of GRS1915+105? - Miller-Jones, James; Rupen, M.; Fender, R.; Rushton, A.; Pooley, G.; Spencer, R. (Wiley-Blackwell Publishing Ltd., 2007)
There is currently a clear discrepancy in the proper motions measured on different angular scales in the approaching radio jets of the black hole X-ray binary GRS 1915+105. Lower velocities were measured with the Very Large Array (VLA) prior to 1996 than were subsequently found from higher resolution observations made with the Very Long Baseline Array and the Multi-Element Radio Linked Interferometer Network. We initiated an observing campaign to use all three arrays to attempt to track the motion of the jet knots from the 2006 February outburst of the source, giving us unprecedented simultaneous coverage of all angular scales, from milliarcsecond scales out to arcsecond scales. The derived proper motion, which was dominated by the VLA measurements, was found to be 17.0 mas d-1, demonstrating that there has been no significant permanent change in the properties of the jets since 1994. We find no conclusive evidence for deceleration of the jet knots, unless this occurs within 70 mas of the core. We discuss possible causes for the varying proper motions recorded in the literature.